Diet composition of data‐limited marlins ( Istiophoridae ) in the Northwest Atlantic - Joseph J. Dello Russo; John M. Logan; Riley Austin; Zachary T. Whitener; Isabelle Sée; Benjamin M. Hurley; Lisa A. Kerr; Joseph M. Quattro; Walter J. Golet (Journal of Fish Biology, 2026)
Knowledge of the dietary composition of Atlantic marlins, especially for recently acknowledged species such as roundscale spearfish ( Tetrapturus georgii ), is limited, as sample access is constrained by international quotas and intermittent landing rates. A series of annual offshore recreational fishing tournaments target Atlantic blue marlin ( Makaira nigricans ), white marlin ( Kajikia albida ) and roundscale spearfish on their seasonal foraging grounds in the South and Mid‐Atlantic Bight. Through this network of tournaments and recreational anglers, we collected stomachs from Atlantic blue marlin ( n = 32), white marlin ( n = 35) and roundscale spearfish ( n = 44) from 2018 to 2020 to investigate general diet composition. Stomach content analysis and DNA barcoding identified a total of 16 prey families across the three focal species, but the majority of prey weight (%W) was from two families (Scombridae and Ommastrephidae). Blue marlin and roundscale spearfish were predominantly piscivorous (99.0 and 80.6%W fishes, respectively), whereas white marlin mainly consumed cephalopods (80%W). The contribution of Scombridae was highest for blue marlin (94.6%W), intermediate for roundscale spearfish (51.7%W) and lowest for white marlin (11%W), with an inverse pattern of relative contribution for Ommastrephidae (0.9, 16.1 and 73.9%W, respectively). Roundscale spearfish and white marlin, despite having a near identical morphology, had diets composed of different prey types in our sample. These dietary data, from three epipelagic apex predators, provide important information for wider ecosystem‐based studies, including in relation to the Mackerel, Squid and Butterfish Fishery Management Plan overseen by the Mid‐Atlantic Fishery Management Council.